Amine modified C3N4 / SiO2 composite material as well as preparation method and application thereof
By preparing amine-modified C3N4/SiO2 composite materials, the problem of poor CO2 adsorption effect due to small specific surface area of SiO2 and carbon nitride materials in the prior art is solved, and a high-efficiency and high selectivity CO2 adsorption effect is achieved.
Patent Information
- Application Number
- CN202510120092.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-25
- Publication Date
- 2025-04-11
AI Technical Summary
In the prior art, the specific surface area of SiO2 and carbon nitride materials is small, resulting in poor adsorption effect of CO2.
By mixing SiO2 and C3N4 precursors and subjecting to ultrasonic, centrifugation, drying and calcining, a C3N4/SiO2 composite material was obtained, and amine-modified by impregnating the organic amine solution was prepared to prepare an amine-modified C3N4/SiO2 composite material.
The amine-modified C3N4/SiO2 composite material has high adsorption amount, high selectivity and low cost. It can efficiently adsorb CO2 under normal pressure and high pressure, solving the problem of poor adsorption effect of traditional adsorbents.
Smart Images

Figure CN119793409A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of carbon capture, and in particular to an amine-modified C3N4 / SiO2 composite material and a preparation method and application thereof. Background Art
[0002] Climate change is a global issue that has attracted widespread attention in recent years. The current climate pattern of the earth is in a state of rising temperatures, melting of polar ice caps, and frequent extreme weather events. In order to mitigate the impact of carbon dioxide emissions on the climate, it is necessary to develop efficient carbon dioxide capture technology. Among the various conventional methods for capturing CO2 such as post-combustion capture, pre-combustion capture, and oxy-combustion capture, post-combustion capture is the most popular one, including chemical absorption, physical absorption, adsorption separation, membrane separation, etc. Adsorption separation is considered to be an attractive option due to its advantages such as high selectivity, easy operation, low energy consumption, and high efficiency.
[0003] SiO2 has good pore organization, controllable structure, easy functionalization and high thermal stability. It is often used as a base material for adsorbents, but its own CO2 adsorption capacity is not high. Carbon nitride materials with inherent high nitrogen content are potential candidate materials for acidic gas adsorption. In its structure, it contains lone pairs of triazine / heptazine rings, which provide Lewis base sites and carbon dioxide, as an acidic molecule, has a great affinity for these base sites. However, its own specific surface area is small, agglomeration is obvious, and the adsorption effect on CO2 is poor.
[0004] Therefore, there is an urgent need for a composite material with high selectivity and the ability to effectively adsorb CO2. Summary of the invention
[0005] The purpose of the present invention is to provide an amine-modified C3N4 / SiO2 composite material and a preparation method and application thereof, so as to solve the technical problems of small specific surface area and poor CO2 adsorption effect in the prior art.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a method for preparing an amine-modified C3N4 / SiO2 composite material, comprising the following steps:
[0008] 1) mixing SiO2 and C3N4 precursors in water to obtain a mixed solution, and then sequentially performing ultrasonic treatment, centrifugation, drying, and calcination to obtain a C3N4 / SiO2 composite material;
[0009] 2) Mixing an organic solvent and an organic amine to obtain an organic amine solution, then adding the C3N4 / SiO2 composite material for impregnation, and drying after the impregnation to obtain an amine-modified C3N4 / SiO2 composite material.
[0010] Furthermore, the C3N4 precursor includes melamine.
[0011] Furthermore, the usage ratio of the SiO2, C3N4 precursor and water is 1g: 0.1-0.5g: 20-30mL.
[0012] Furthermore, in the step 1), the ultrasonic time is 0.5 to 2 hours;
[0013] The drying temperature is 70-90°C;
[0014] The calcination temperature is 500-600° C., and the calcination time is 2-6 hours.
[0015] Further, the organic solvent includes methanol;
[0016] The organic amine includes diethylenetriamine.
[0017] Furthermore, the concentration of the organic amine solution is 1 to 5 mol / L;
[0018] The volume mass ratio of the organic amine solution and the C3N4 / SiO2 composite material is 20 mL: 0.3-0.5 g.
[0019] Furthermore, in the step 2), the immersion is carried out under stirring, and the immersion time is 1 to 5 hours.
[0020] Furthermore, in the step 2), the drying temperature is 60-100°C.
[0021] The invention provides an amine-modified C3N4 / SiO2 composite material prepared by the preparation method.
[0022] The present invention also provides an application of the amine-modified C3N4 / SiO2 composite material in adsorbing CO2 in industrial flue gas.
[0023] Beneficial effects of the present invention:
[0024] 1) The amine-modified C3N4 / SiO2 composite material prepared by the present invention has the advantages of high adsorption capacity, simple preparation method, high selectivity, superior performance and low cost. The amine-modified porous material solid adsorbent can adsorb CO2 with high selectivity through chemical action, which is basically not affected by other gases, water and temperature, and can solve the problems existing in conventional solid adsorbents; at the same time, the amine-modified C3N4 / SiO2 composite material has well-developed pores, which is easy for gas molecules to diffuse, and can also solve the problems such as mass transfer difficulties caused by the high viscosity of the liquid amine solution in the absorption method, thereby greatly improving the adsorption efficiency;
[0025] 2) The raw materials SiO2 and melamine used in the present invention are low in cost, and the preparation process of the composite material is simple and can be mass-produced;
[0026] 3) The adsorption capacity of CO2 by the amine-modified C3N4 / SiO2 composite material under high pressure is much higher than that under normal pressure, and pressure swing adsorption can be used to realize the industrial application of CO2 capture; the adsorption performance of CO2 under normal pressure is significantly higher than that of the C3N4 / SiO2 composite material that has not been amine-modified, thereby improving the adsorption effect of the adsorbent under normal pressure. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The nitrogen isothermal adsorption-desorption curve of the C3N4 / SiO2 composite material prepared in Example 1;
[0028] Figure 2 XRD pattern of the C3N4 / SiO2 composite material prepared in Example 1;
[0029] Figure 3 The nitrogen isothermal adsorption-desorption curve of the amine-modified C3N4 / SiO2 composite material prepared in Example 1;
[0030] Figure 4 XRD pattern of the amine-modified C3N4 / SiO2 composite material prepared in Example 1;
[0031] Figure 5 The CO2 adsorption breakthrough curves of the C3N4 / SiO2 composite materials with different mixing ratios prepared in Examples 1 to 5;
[0032] Figure 6 Graphs showing the CO2 adsorption of C3N4 / SiO2 composite materials with different mixing ratios prepared in Examples 1 to 5;
[0033] Figure 7 The graph of CO2 adsorption of amine-modified C3N4 / SiO2 composite materials at different concentrations of organic amine solutions prepared in Examples 1 and Examples 6 to 9;
[0034] Figure 8 This is a graph of the CO2 adsorption capacity of the amine-modified C3N4 / SiO2 composite material prepared in Example 1 under different pressures. DETAILED DESCRIPTION
[0035] The present invention provides a method for preparing an amine-modified C3N4 / SiO2 composite material, comprising the following steps:
[0036] 1) mixing SiO2 and C3N4 precursors in water to obtain a mixed solution, and then sequentially performing ultrasonic treatment, centrifugation, drying, and calcination to obtain a C3N4 / SiO2 composite material;
[0037] 2) Mixing an organic solvent and an organic amine to obtain an organic amine solution, then adding the C3N4 / SiO2 composite material for impregnation, and drying after the impregnation to obtain an amine-modified C3N4 / SiO2 composite material.
[0038] In the present invention, the C3N4 precursor is preferably melamine.
[0039] In the present invention, the usage ratio of the SiO2, C3N4 precursor and water is 1g: 0.1-0.5g: 20-30mL, preferably 1g: 0.2-0.4g: 22-28mL, and further preferably 1g: 0.3-0.4g: 24-26mL.
[0040] In the present invention, in the step 1), the ultrasonic time is 0.5 to 2 hours, preferably 0.8 to 1.5 hours, and more preferably 1 hour;
[0041] The drying temperature is 70-90°C, preferably 75-85°C, and more preferably 80°C;
[0042] The calcination temperature is 500-600° C., preferably 520-580° C., and more preferably 550° C.; the calcination time is 2-6 hours, preferably 3-5 hours, and more preferably 4 hours.
[0043] In the present invention, the organic solvent is preferably methanol;
[0044] The organic amine is preferably diethylenetriamine.
[0045] In the present invention, the concentration of the organic amine solution is 1 to 5 mol / L, preferably 2 to 4 mol / L, and more preferably 3 mol / L;
[0046] The volume mass ratio of the organic amine solution and the C3N4 / SiO2 composite material is 20 mL: 0.3-0.5 g, preferably 20 mL: 0.35-0.45 g, and further preferably 20 mL: 0.4 g.
[0047] In the present invention, in the step 2), the immersion is carried out under stirring, and the immersion time is 1 to 5 hours, preferably 2 to 4 hours, and more preferably 3 hours.
[0048] In the present invention, in the step 2), the drying temperature is 60 to 100°C, preferably 70 to 90°C, and more preferably 80°C.
[0049] The invention provides an amine-modified C3N4 / SiO2 composite material prepared by the preparation method.
[0050] The present invention also provides an application of the amine-modified C3N4 / SiO2 composite material in adsorbing CO2 in industrial flue gas.
[0051] In the present invention, the specific method of using the amine-modified C3N4 / SiO2 composite material for adsorbing CO2 in industrial flue gas is as follows: a fixed bed adsorption device is used to determine the adsorption penetration curve of the modified material for CO2, and 0.3g of dry sample is loaded into an adsorption column (Φ=6mm, L=300mm). The intake flow rate of the simulated mixed gas of CO2 and N2 (CO2 concentration is 15%) is 10-60mL / min, the adsorption temperature is 20-60°C, and the adsorption pressure is 0.1-0.5MPa; the CO2 adsorption and regeneration performance are determined by 4 processes of purging, gas distribution, adsorption, and regeneration. The tail gas components are detected in real time by a CO2 analyzer. The regeneration conditions are 30mL / minAr purging and desorption temperature of 110-120°C, until all the CO2 in the adsorbent in the fixed bed is purged, and the CO2 concentration of the infrared gas analyzer is 0, then the adsorbent is regenerated.
[0052] The carbon dioxide adsorption breakthrough curve is plotted and the saturated adsorption capacity Q is calculated based on the curve:
[0053]
[0054] In formula 1, Q is the saturated adsorption capacity, mg / g; M is the relative molecular mass of carbon dioxide, 44.01 g / mol; V is the volume flow rate of the inlet mixed gas, mL / min; C0 is the carbon dioxide concentration in the inlet mixed gas (volume percentage); C is the carbon dioxide concentration in the adsorbed tail gas (volume percentage); m 吸 is the mass of amine-modified C3N4 / SiO2 composite material, g; V m is the standard gas molar volume, 22400mL / mol.
[0055] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0056] Example 1
[0057] A method for preparing an amine-modified C3N4 / SiO2 composite material comprises the following steps:
[0058] 1 g of SiO2 was mixed in 25 mL of water, and then 0.2 g of melamine (the manufacturer of melamine was Shanghai MacLean Biochemical Technology Co., Ltd.) was added, and the mixture was completely mixed by ultrasonication for 1 h to obtain a mixed solution, and the mixed solution was centrifuged and dried at 80°C, and then placed in a tube furnace and calcined at 550°C for 4 h to obtain a C3N4 / SiO2 composite material (the mixing ratio of C3N4 / SiO2 was 20%);
[0059] The prepared C3N4 / SiO2 composite material was tested, and the test results are as follows Figures 1-2 shown. Figure 1 The nitrogen isothermal adsorption-desorption curve of the C3N4 / SiO2 composite material prepared in Example 1; Figure 2 The XRD pattern of the C3N4 / SiO2 composite material prepared in Example 1. Figure 1 It can be seen that the nitrogen isothermal adsorption-desorption curves of SiO2, C3N4 and the synthesized C3N4 / SiO2 composite material are all rare Langmuir III type curves, and the hysteresis loop is H3 type. The pore structure is very irregular, and the amount of adsorbed gas increases with the increase of the partial pressure of the component. The adsorption heat of the first layer is smaller than the liquefaction heat of the adsorbate, so that the adsorbate is difficult to adsorb in the initial stage of adsorption. As the adsorption process proceeds, the adsorption appears self-acceleration, and the number of adsorption layers is not limited. Figure 2 It can be seen that the XRD spectra of SiO2 and the synthesized C3N4 / SiO2 composite material are both dome-shaped scattering curves, and the structure is amorphous. The XRD spectrum of C3N4 has two characteristic diffraction peaks at 2θ=13.18° and 27.48°, corresponding to the in-plane triazine stacking and interlayer stacking of the conjugated aromatic system, respectively, indicating that the obtained product is layered graphite phase carbon nitride. The addition of a small amount of C3N4 does not change the overall crystal structure of the composite material, and it still maintains an amorphous state.
[0060] Diethylenetriamine was dissolved in methanol to obtain a diethylenetriamine solution with a concentration of 2 mol / L; 0.4 g of C3N4 / SiO2 composite material was placed in 20 mL of diethylenetriamine solution and immersed for 3 hours, centrifuged, and finally dried at 80°C. After drying, an amine-modified C3N4 / SiO2 composite material was obtained.
[0061] The prepared amine-modified C3N4 / SiO2 composite material was tested, and the test results are as follows: Figures 3-4 shown. Figure 3 The nitrogen isothermal adsorption-desorption curve of the amine-modified C3N4 / SiO2 composite material prepared in Example 1; Figure 4 The XRD pattern of the amine-modified C3N4 / SiO2 composite material prepared in Example 1. Figure 3 It can be seen that the nitrogen isothermal adsorption-desorption curves of the synthesized C3N4 / SiO2 composite material and the amine-modified C3N4 / SiO2 composite material are both rare Langmuir type III curves, and the hysteresis loop is H3 type. Because the amine is loaded on the surface of the composite material, its specific surface area is reduced. Figure 4 It can be seen that the XRD spectra of SiO2, synthesized C3N4 / SiO2 composite materials and amine-modified C3N4 / SiO2 composite materials are all dome-shaped scattering curves, and the structure is amorphous. The addition of diethylenetriamine does not change the crystal structure of the composite material.
[0062] Embodiments 2 to 5
[0063] Compared with Example 1, the difference is that the added amounts of melamine are 0.1g, 0.3g, 0.4g and 0.5g respectively, that is, the mixing ratios of C3N4 / SiO2 are 10%, 30%, 40% and 50% respectively.
[0064] The C3N4 / SiO2 composite materials with different mixing ratios prepared in Examples 1 to 5 were used to adsorb CO2 in industrial flue gas. The test method was as follows: the CO2 concentration of the simulated industrial exhaust gas was 15%, the adsorbent material was placed in a fixed bed, and adsorption was performed under the conditions of a C3N4 / SiO2 mixing ratio of 20%, an air flow rate of 20 mL / min, an adsorption temperature of 25°C, and normal pressure. The test results are shown in FIG. Figures 5-6 As shown. Figure 5 , Figure 6 It can be seen that the C3N4 / SiO2 composite material with a mixing ratio of 20% has the longest penetration time and the largest adsorption capacity, and the maximum saturated adsorption capacity is 99.13 mg / g. The adsorption capacity of CO2 by C3N4 and SiO2 alone is poor. Mixing the two in an appropriate ratio can play a synergistic role in increasing their adsorption performance.
[0065] Embodiments 6 to 9
[0066] Compared with Example 1, the difference is that the concentrations of the organic amine solutions are 1 mol / L, 3 mol / L, 4 mol / L and 5 mol / L respectively.
[0067] The amine-modified C3N4 / SiO2 composite material prepared by Example 1 and Examples 6 to 9 is used to adsorb CO2 in industrial flue gas. The specific method is as follows: a fixed bed adsorption device is used to determine the adsorption penetration curve of the modified material for CO2, and 0.3g of the amine-modified C3N4 / SiO2 composite material is loaded into an adsorption column (Φ=6mm, L=300mm). The intake flow rate of the simulated mixed gas of CO2 and N2 (CO2 concentration is 15%) is 20mL / min, the adsorption temperature is 40°C, and the adsorption pressure is normal pressure; the CO2 adsorption and regeneration performance are determined by purging, gas distribution, adsorption, and regeneration. The tail gas components are detected in real time by a CO2 analyzer. The regeneration conditions are 30mL / minAr purge and desorption temperature of 110°C, until all the CO2 in the adsorbent in the fixed bed is purged, and the CO2 concentration of the infrared gas analyzer is 0, then the adsorbent is regenerated.
[0068] The carbon dioxide adsorption breakthrough curve is plotted and the saturated adsorption capacity Q is calculated based on the curve:
[0069]
[0070] In formula 1, Q is the saturated adsorption capacity, mg / g; M is the relative molecular mass of carbon dioxide, 44.01 g / mol; V is the volume flow rate of the inlet mixed gas, mL / min; C0 is the carbon dioxide concentration in the inlet mixed gas (volume percentage); C is the carbon dioxide concentration in the adsorbed tail gas (volume percentage); m 吸 is the mass of amine-modified C3N4 / SiO2 composite material, g; V m is the standard gas molar volume, 22400mL / mol. The test results are as follows Figure 7 shown.
[0071] The amine-modified C3N4 / SiO2 composite material of Example 1 was adsorbed at pressures of 0.1MPa, 0.2MPa, 0.3MPa, 0.4MPa, and 0.5MPa, respectively, using a diethylenetriamine solution with an impregnation concentration of 2mol / L, an air flow rate of 20mL / min, and an adsorption temperature of 40°C. The test results are shown in FIG. Figure 8 shown.
[0072] from Figure 7 and Figure 8 It can be seen that the adsorption effect of the amine-modified composite material at normal pressure is much higher than that of the simple unmodified composite material, reaching 309.1 mg / g. Under normal pressure environment, chemical adsorption plays a key role. With the increase of pressure, the single-layer chemical adsorption terminates, and the multi-layer physical adsorption of the composite material plays a role. The maximum saturated adsorption capacity of CO2 is 639.91 mg / g.
[0073] As can be seen from the above embodiments, the present invention provides an amine-modified C3N4 / SiO2 composite material and its preparation method and application, wherein SiO2 and C3N4 precursor are mixed in water to obtain a mixed solution, and then ultrasonic, centrifugal, drying and calcining are performed in sequence to obtain a C3N4 / SiO2 composite material; an organic solvent and an organic amine are mixed to obtain an organic amine solution, and then the C3N4 / SiO2 composite material is added for impregnation, and then dried after the impregnation to obtain an amine-modified C3N4 / SiO2 composite material. The amine-modified C3N4 / SiO2 composite material of the present invention has a maximum saturated adsorption capacity of 639.91 mg / g for CO2 under the conditions of an intake flow rate of 20 mL / min, an adsorption temperature of 40°C and 0.5 MPa.
[0074] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing an amine-modified C3N4 / SiO2 composite material, characterized in that: The following steps are involved: 1) mixing SiO2 and C3N4 precursors in water to obtain a mixed solution, and then sequentially performing ultrasonic treatment, centrifugation, drying, and calcination to obtain a C3N4 / SiO2 composite material; 2) Mixing an organic solvent and an organic amine to obtain an organic amine solution, then adding the C3N4 / SiO2 composite material for impregnation, and drying after the impregnation to obtain an amine-modified C3N4 / SiO2 composite material.
2. The method for preparing the amine-modified C3N4 / SiO2 composite material according to claim 1, characterized in that: The C3N4 precursor includes melamine.
3. The method for preparing the amine-modified C3N4 / SiO2 composite material according to claim 1 or 2, characterized in that: The usage ratio of the SiO2, C3N4 precursor and water is 1g: 0.1-0.5g: 20-30mL.
4. The method for preparing the amine-modified C3N4 / SiO2 composite material according to claim 3, characterized in that: In the step 1), the ultrasonic time is 0.5 to 2 hours; The drying temperature is 70-90°C; The calcination temperature is 500-600° C., and the calcination time is 2-6 hours.
5. The method for preparing the amine-modified C3N4 / SiO2 composite material according to claim 4, characterized in that: The organic solvent includes methanol; The organic amine includes diethylenetriamine.
6. The method for preparing the amine-modified C3N4 / SiO2 composite material according to claim 5, characterized in that: The concentration of the organic amine solution is 1 to 5 mol / L; The volume mass ratio of the organic amine solution and the C3N4 / SiO2 composite material is 20 mL: 0.3-0.5 g.
7. The method for preparing the amine-modified C3N4 / SiO2 composite material according to claim 5 or 6, characterized in that: In the step 2), the immersion is carried out while stirring, and the immersion time is 1 to 5 hours.
8. The method for preparing the amine-modified C3N4 / SiO2 composite material according to claim 7, characterized in that: In the step 2), the drying temperature is 60-100°C.
9. An amine-modified C3N4 / SiO2 composite material prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the amine-modified C3N4 / SiO2 composite material according to claim 9 in adsorbing CO2 in industrial flue gas.